In vitro antioxidant and enzyme inhibitory studies, computational analysis and chemodiversity of an emergency food plant Caralluma edulis (Edgew.) Benth. ex Hook.f: A multifunctional approach to provide new ingredients for nutraceuticals and functional foods. (December 2022) - Shazmeen, Natasha; Nazir, Mamona; Riaz, Naheed; Saleem, Muhammad; Tousif, Muhammad Imran; Tauseef, Saba; Uddin, Reaz; Mukhtar, Mahreen; Zengin, Gokhan; Mollica, Adriano; A. Zarbah, Abdulaziz; Alarfaji, Saleh S.; et al.
Abstract: Caralluma edulis is a leafless succulent herb native to India and Pakistan, where it is used as emergency food and as potential herbal medicine. It was investigated for its bioactive chemicals and further medicinal properties. The objective of the current study was to accomplish the chemical and biological characterization of C. edulis . Chemical profiling was done through estimation of total bioactive contents and UHPLMS analysis. Biological screening was achieved through six different antioxidant and enzyme inhibition assays. Estimation of its phenolic and flavonoid contents revealed that ethyl acetate fraction (Ce-E) contains 14.15 mg GAE/g extract and 26.13 mg RE/g extract of phenolics and flavonoids, respectively, followed by the methanolic (Ce-M) and the water (Ce-W) soluble fractions. In free radical inhibitory assays, Ce-E fraction also exhibited highest activity (DPPH: 19.72 mg TE/g extract, ABTS: 48.66 mg TE/g extract) followed by Ce-M, whereas, in CUPRAC and FRAP assays, all the extracts, except water fraction, exhibited nearly equal potential in the range of 53.85–57.96 and 25.42–32.12 mg TE/g extract, respectively. In metal chelating antioxidant assay, only Ce-M and Ce-W fractions displayed considerable activities (25.88 and 23.55 mg EDTAE/g extract respectively), whereas, Ce-H exhibited the highest activity in phosphomolybdenum assay (1.03 mmolTE/g extract), against BChE (6.43 mg GALAE/g extract), α-glucosidase and α-amylase (6.98 and 0.47 mmol ACAE/g, respectively) and tyrosinase (64.46 mg KAE/g extract) enzymes. Ce-M and Ce-E also exhibited significant activity against tyrosinase (59.85 and 58.40 mg KAE/g extract, respectively). Crude methanolic extract (Ce-M) was analyzed to unveil its secondary metabolic picture; the UHPLCMS analysis discloses 105 compounds as phenolic acids, flavonoids, steroids and their glycosides, which makes the C. edulis extract a strong candidate for nutraceutical and functional food ingredient. Some of the metabolites were docked against all the tested enzymes to predict mode of actions and to substantiate the pharmaceutical nature of C. edulis .